Ang lola kong mahilig mag-utos - Gatmaitan, Luis P.; Bascon, Zeus; Chong, Grace Dacanay (Quezon City LG & M Corporation, 2013)
Ang Lola Kong Mahilig Mag-utos is a story that shows what aging grandparents go through.
"Ages 3-6 y.o."
Text in English and Filipino.
Keywords: Grandmothers -- Philippines -- Juvenile literature; Children's stories, Philippine (English)